Spatial dissociation between two endogeic earthworms in the Colombian "Llanos" - Jiménez Jaén, J.J.; Rossi, J.P. (2006)
Although there has been a growing interest in the study of soil fauna spatial distribution during the past decade, the identification of the environmental driving factors behind the population patterning are difficult to highlight. Soil physico-chemical heterogeneity is partly responsible for structuring the population. However, the available statistical analyses show that the proportion of the population spatial variance that can be ascribed to soil habitat variability is modest. We studied the spatial distribution of two medium-sized endogeic earthworm species (Andiodrilus sp. and Glossodrilus sp.) and the spatial segregation between them. The survey was undertaken in a native savanna and a grass-legume pasture in the Colombian Llanos . The presence of spatial dependence in the data (i.e. earthworm counts) was tested using two different approaches: the Spatial Analysis using Distance IndicEs (SADIE) analyses and cross-coregionalization. The SADIE index allowed for testing the spatial association or dissociation between earthworm counts. The spatial organization of both species was well structured in the natural savanna while they were randomly distributed in the pasture in almost all sampling dates. When the spatial distribution was different from randomness it was always aggregated irrespective of the land-use system. There was no absolute stable spatial pattern in the natural savanna although a general pattern seemed to emerge. On the contrary, no pattern was observed in the pasture. Both species displayed opposite spatial distributions (P < 0.05) that were of different intensity depending on the sampling date. The presence of opposite patches and gaps suggests the presence of a competitive exclusion phenomenon (at least spatial) that deserves further investigations.